2015
DOI: 10.1007/s00395-015-0461-1
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 inhibition rescues β1-adrenergic cardiomyopathy by reducing myocyte necrosis and non-myocyte apoptosis rather than myocyte apoptosis

Abstract: It is generally held that inhibition of mammalian sterile 20-like kinase 1 (Mst1) protects the heart through reducing myocyte apoptosis. We determined whether inhibition with a dominant-negative Mst1 (DN-Mst1) would protect against the cardiomyopathy induced by chronic β1-adrenergic receptor (β1-AR) stimulation by preventing myocyte apoptosis. DN-Mst1 mice were mated with β1-AR transgenic (Tg) mice and followed for 20 months. β1-AR Tg mice developed cardiomyopathy as they aged, as reflected by premature mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
8
27
0
Order By: Relevance
“…Nonetheless, our current study for the first time provided the evidence that MT2 but not MT1 is a newly identified cardiac guardian receptor against MI/R injury. Besides, our current study failed to distinguish between myocyte and nonmyocyte apoptosis in the evaluation of cardiac apoptosis as established by previous reports, but the beneficial effects of melatonin in cardiac apoptosis inhibition might not be limited to cardiomyocytes according to previous studies . Additionally, as for the possible role and downstream signaling of MT1 in cardiomyocytes, this was a very interesting issue.…”
Section: Discussionmentioning
confidence: 56%
“…Nonetheless, our current study for the first time provided the evidence that MT2 but not MT1 is a newly identified cardiac guardian receptor against MI/R injury. Besides, our current study failed to distinguish between myocyte and nonmyocyte apoptosis in the evaluation of cardiac apoptosis as established by previous reports, but the beneficial effects of melatonin in cardiac apoptosis inhibition might not be limited to cardiomyocytes according to previous studies . Additionally, as for the possible role and downstream signaling of MT1 in cardiomyocytes, this was a very interesting issue.…”
Section: Discussionmentioning
confidence: 56%
“…Cardiac Mst1 is up‐regulated in experimental models of MI (Odashima et al, ), pathological hypertrophy (Odashima et al, ), arrhythmic cardiomyopathy (Chen et al, ), diabetic cardiomyopathy (Hu et al, ), or cardiomyopathy due to cardiac overexpression of β 1 ‐ or β 2 ‐adrenoceptors (Chen et al, ; Lee, Yan, Vatner, & Vatner, ; Peter et al, ; Zhao et al, ). In cardiac biopsy samples from patients with DCM or arrhythmogenic cardiomyopathy, and HF due to ischaemic cardiomyopathy or DCM, YAP phosphorylation at Ser 127 is increased implying activation of the Hippo signalling pathway (Chen et al, ; Hou et al, ; Leach et al, ).…”
Section: Activation Of β‐Adrenoceptors Upregulates Gal‐3 Expression Imentioning
confidence: 99%
“…Lee et al studied the effect of cardiomyocyte‐specific inactivation of Mst1 in the β 1 ‐TG cardiomyopathy model by crossing the β 1 ‐TG mice with dnMst1‐TG mice to generate dual TG mice and mice with control genotypes (Lee et al, ). They studied cardiac phenotype in animals at 18–20 months of age and revealed inhibition by approximately 60% of cardiomyocyte apoptosis and myocardial fibrosis together with improved LV function and survival (Lee et al, ). In Mst1 gene deleted mice, similar protection against cardiotoxicity by isoprenaline treatment (60 mg −1 ·kg −1 ·day −1 for 24 hr via minipump) was observed (Lee et al, ).…”
Section: Activation Of β‐Adrenoceptors Upregulates Gal‐3 Expression Imentioning
confidence: 99%
“…A possible explanation is that isoproterenol may promote cell survival or death in a dose-dependent fashion via activation of distinct pathways: treatment with low-dose isoproterenol enhances cell survival by increasing ERK1/2-mediated expression of Bcl-2, while stimulation with high concentration of isoproterenol leads to cell death through PKA-dependent downregulation of Bcl-2 [140]. Interestingly, chronic β 1-AR stimulation by transgenic expression of β 1-AR or by isoproterenol injection also resulted in necrotic myocyte death that is dependent on mammalian Ste20-like kinase 1 (Mst1) [151]. …”
Section: Gpcrmentioning
confidence: 99%